PEMANFAATAN MEDIA INTERACTIVE FLAT PANEL DISPLAY (IFPD) DALAM PEMBELAJARAN IPS BAGI SISWA MADRASAH - Riyadi, Rachman; Ningsih, Tutuk (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The increasingly advanced development of technology has had a very rapid impact on all aspects of human life, including in the fields of knowledge and education. Technology in the field of education is one of the media supporting the implementation of education itself, one of which is the use of Interactive Flat Panel Display (IFPD) media. The aim of this research is to examine in more depth the use of Interactive Flat Panel Display (IFPD) media in Social Studies Learning for Madrasah Students. This research was conducted at MI Darwata Sikampuh, with the research subjects being fifth grade teachers and students, and the research object was the use of IFPD in social studies learning. This research is a qualitative descriptive research, with the type of field research (Filed Research). Data collection was carried out by means of observation, interviews and documentation. Data analysis was carried out using the Miles Huberman technique by reducing the data first, presenting the reduced data, and drawing conclusions and verification. The results of this research show that the use of Interactive Flat Panel Display (IFPD) media in social studies learning has a positive impact on students, this is shown by the students' learning motivation.